EFEKTIVITAS EKSTRAK DAUN JATI ( TECTONA GRANDIS L. F) DALAM MENGHAMBAT PERTUMBUHAN JAMUR HORMISCIUM Sp. - Astiti, Ni Putu Adriani (Bumi Lestari, 2016)
A research on effectiveness of extracts of teak (Tectona grandis L. f) leaves in inhibit the growth of a species of fungi, Hormiscium sp. has been carried out.  The leaves used in this research were young leaves (number 1 and 2), and old ones (number 5 and 6), with four concentrations: 0, 2, 5, and 10 %.  The media utilised were bean sprouts agar, and the replications was 3 times.  Qualitative tests were undertaken for the flavonoids, while alkaloid tests were based on Culvenor Fitzgerald methods.  Qualitative tests of triterpenoids and steroids were undertaken by utilising Lieberman – Burchard reagents (L-B reagents). Parameters observed were colony diameters, micellium weights (dry mass), and numbers of conidia (ml ).  Results of this research showed that extracts of teak (T. grandis) leaves were able to inhibit the growth of Hormiscium sp.  The capability of inhibitions was increased as the extract concentrations increased (for both, that of the young and old leaves), even though extracts of the young provided a higher capability of inhibitions compared to the old ones.
Keywords: teak (Tectona grandis Lf), leaves extracts, Hormiscium sp